EDUKASI PERSONAL HYGIENE PADA PEKERJA PENANGANAN PRASARANA DAN SARANA UMUM (PPSU) - Lestari, Ade Dwi; Ridwan, Alvin Mohamad; Hairunisa, Nany; Khairani, Rita; Khairunisa, Adinda; Kencana, Gita; Iskandar, Dian (Jurnal Pengabdian Masyarakat Trimedika, 2025)
Personal hygiene is a crucial component of occupational health, particularly for sanitation workers, including Public Infrastructure and Facility Handling (PPSU) workers in Rawa Buaya Village. This community service project aimed to provide education and assess the knowledge and awareness of PPSU workers regarding personal hygiene, with a focus on handwashing. The activity included counseling sessions, pre- and post-tests, and the distribution of educational materials such as posters and presentations. The results showed a significant improvement in workers' knowledge, with an average post-test score increase of 37.68%. These findings highlight the importance of continuous occupational health education to enhance hygiene practices and reduce health risks among PPSU workers